Descriptive Epidemiology and Outcomes of Nonventilated Hospital-Acquired, Ventilated Hospital-Acquired, and Ventilator-Associated Bacterial Pneumonia in the United States, 2012–2019. Issue 3 (17th September 2021) - Zilberberg, Marya D.; Nathanson, Brian H.; Puzniak, Laura A.; Shorr, Andrew F.
Abstract : OBJECTIVES: Multiple randomized controlled trials exploring the outcomes of patients with ventilator-associated bacterial pneumonia and hospital-acquired bacterial pneumonia have noted that hospital-acquired bacterial pneumonia patients who require subsequent ventilated hospital-acquired bacterial pneumonia suffered higher mortality than either those who did not (nonventilated hospital-acquired bacterial pneumonia) or had ventilator-associated bacterial pneumonia. We examined the epidemiology and outcomes of all three conditions in a large U.S. database. DESIGN: Retrospective cohort. SETTING: Two hundred fifty-three acute-care hospitals, United States, contributing data (including microbiology) to Premier database, 2012–2019. PATIENTS: Patients with hospital-acquired bacterial pneumonia or ventilator-associated bacterial pneumonia identified based on a slightly modified previously published International Classification of Diseases, 9th Edition/ International Classification of Diseases, 10th Edition-Clinical Modification algorithm. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Among 17, 819 patients who met enrollment criteria, 26.5% had nonventilated hospital-acquired bacterial pneumonia, 25.6% vHAPB, and 47.9% ventilator-associated bacterial pneumonia. Ventilator-associated bacterial pneumonia predominated in the Northeastern United States and in large urban teaching hospitals. Patients with nonventilated hospital-acquired bacterial pneumonia were oldest (mean 66.7 ± 15.1 yr) and most likely White (76.9%), whereas those with ventilator-associated bacterial pneumonia were youngest (59.7 ± 16.6 yr) and least likely White (70.3%). Ventilated hospital-acquired bacterial pneumonia was associated with the highest comorbidity burden (mean Charlson score 4.1 ± 2.8) and ventilator-associated bacterial pneumonia with the lowest (3.2 ± 2.5). Similarly, hospital mortality was highest among patients with ventilated hospital-acquired bacterial pneumonia (29.2%) and lowest in nonventilated hospital-acquired bacterial pneumonia (11.7%), with ventilator-associated bacterial pneumonia in-between (21.3%). Among survivors, 24.5% of nonventilated hospital-acquired bacterial pneumonia required a rehospitalization within 30 days of discharge, compared with 22.5% among ventilated hospital-acquired bacterial pneumonia and 18.8% ventilator-associated bacterial pneumonia. Unadjusted hospital length of stay after infection onset was longest among ventilator-associated bacterial pneumonia and shortest among nonventilated hospital-acquired bacterial pneumonia patients. Median total hospital costs mirrored length of stay: ventilator-associated bacterial pneumonia $77, 657, ventilated hospital-acquired bacterial pneumonia $62, 464, and nonventilated hospital-acquired bacterial pneumonia $39, 911. CONCLUSIONS: Both hospital-acquired bacterial pneumonia and ventilator-associated bacterial pneumonia remain associated with significant mortality and cost in the United States. Our analyses confirm that of all three conditions, ventilated hospital-acquired bacterial pneumonia carries the highest risk of death. In contrast, ventilator-associated bacterial pneumonia remains most costly. Nonventilated hospital-acquired bacterial pneumonia survivors were most likely to require a readmission within 30 days of discharge.